A Parallel Energy-Sharing Control Strategy for Fuel Cell Hybrid Vehicle - Jenn Hwa Wong; Tole Sutikno; Nik Rumzi Nik Idris; Makbul Anwari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
This paper presents a parallel energy-sharing control strategy for the application of fuel cell hybrid vehicles (FCHVs). The hybrid source discussed consists of a fuel cells (FCs) generator and energy storage units (ESUs) which composed by the battery and ultracapacitor (UC) modules. A direct current (DC) bus is used to interface between the energy sources and the electric vehicles (EV) propulsion system (loads). Energy sources are connected to the DC bus using of power electronics converters. A total of six control loops are designed in the supervisory system in order to regulate the DC bus voltage, control of current flow and to monitor the state of charge (SOC) of each energy storage device at the same time. Proportional plus integral (PI) controllers are employed to regulate the output from each control loop referring to their reference signals. The proposed energy control system is simulated in MATLAB/Simulink environment. Results indicated that the proposed parallel energy-sharing control system is capable to provide a practical hybrid vehicle in respond to the vehicle traction response and avoids the FC and battery from overstressed at the same time.